From Thought to Text: A Psycholinguistic Study of Students’ Language Processing in Creative Writing Class - Bakri, Fitriyani; Nasta, Mardiyanah; Mutmainna Halim, Nur; Fauzi, Rizki (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
Writing is a complicated psycholinguistic task that changes thoughts inside your head into ordered words. In EFL situations, this process necessitates meticulous coordination of cognitive and linguistic resources, frequently resulting in challenges in lexical retrieval, grammatical encoding, and idea development. This study examines the cognitive processing of language by students when they create imaginative texts inspired by visual stimuli. The study, based on Levelt’s (1999) Model of Language Production, examines the processes of conceptualization, formulation, articulation, and self-monitoring in students’ writing. Thirty-five English Literature students from class B 2022 at Universitas Negeri Makassar took part in the creative writing exercise. Five students with the fewest errors and five students with the most errors were chosen for in-depth semi-structured interviews. The results show that students who do well have better conceptual planning and self-monitoring skills, while those who do poorly have trouble with formulation, especially with choosing words and structuring sentences. The study underscores the significance of psycholinguistic awareness in enhancing EFL creative writing training, focusing on tactics that bolster cognitive control and linguistic accuracy.